2015
DOI: 10.1016/j.neuroimage.2015.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Group differences in MEG-ICA derived resting state networks: Application to major depressive disorder

Abstract: Functional magnetic resonance imaging (fMRI) studies have revealed the existence of robust, interconnected brain networks exhibiting correlated low frequency fluctuations during rest, which can be derived by examining inherent spatio-temporal patterns in functional scans independent of any a priori model. In order to explore the electrophysiological underpinnings of these networks, analogous techniques have recently been applied to magnetoencephalography (MEG) data, revealing similar networks that exhibit corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 68 publications
5
83
3
Order By: Relevance
“…The state of a given emotional network along this curve is modulated by PFC inputs to AMY since this PFC-AMY circuit is altered by chronic stress and direct stimulation of this circuitry using DREADDs. Given that deficits in functional connectivity across PFC-dependent networks have been described in major depressive disorder (Greicius et al, 2007; Nugent et al, 2015), activity across the P-AV network may serve as a novel translational measure of face validity in preclinical models of major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The state of a given emotional network along this curve is modulated by PFC inputs to AMY since this PFC-AMY circuit is altered by chronic stress and direct stimulation of this circuitry using DREADDs. Given that deficits in functional connectivity across PFC-dependent networks have been described in major depressive disorder (Greicius et al, 2007; Nugent et al, 2015), activity across the P-AV network may serve as a novel translational measure of face validity in preclinical models of major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
“…1(B). Firstly, preprocessed data from individuals was normalized to z values (to account for inter-subject variations) and temporally concatenated across all subjects, which has been widely used in ICA to identify networked brain activity in group analysis (Chen et al, 2013; Ding et al, 2014; Nugent et al, 2015; Ponomarev et al, 2014; Ramkumar et al, 2014; Yuan et al, 2012), assuming spatial similarity across subjects. Secondly, power spectra in the range of 2 Hz to 30 Hz at a 1 Hz resolution were calculated via a short-time Fourier transform (STFT) on individual 1-s EEG epochs, and then obtained time-frequency EEG (epochs × power spectra) data were decomposed into 32 ICs using tfICA (Bingham and Hyvarinen, 2000; Shou et al, 2012) 1 , after an initial data reduction using principal component analysis (PCA).…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim of this preliminary study was to assess the overall effects of ketamine on connectivity in MDD subjects, as our sample size was too limited to assess responders versus non-responders. Although we already reported the baseline effects of ketamine in a larger cohort that overlapped with this one (Nugent et al, 2015b), we felt that the additional scans acquired post-ketamine infusion justified further analysis, albeit preliminary and hypothesis-generating in nature. The formulation of hypotheses in this area is difficult given the dearth of research using resting state MEG to study MDD, as well as the lack of literature investigating the effects of ketamine on connectivity in subjects with MDD at a time point corresponding to its antidepressant effects.…”
Section: Introductionmentioning
confidence: 98%
“…We previously found that this method can be extended to group analyses (Nugent et al, 2015b). Comparing healthy subjects to subjects with MDD at baseline, we found reduced connectivity between the sgACC and a bilateral precentral independent component (IC), as well as increased amygdalar connectivity with insulo-temporal ICs in individuals with MDD (Nugent et al, 2015b). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation